Translating Policy into Practice for Community-Based Management of Rheumatoid Arthritis: Targeting Professional Development Needs among Physiotherapists. (11th November 2012) - Fary, Robyn E.; Slater, Helen; Chua, Jason; Briggs, Andrew M.
Abstract : Introduction . Contemporary health policy promotes delivery of community-based health services to people with musculoskeletal conditions, including rheumatoid arthritis (RA). This emphasis requires a skilled workforce to deliver safe, effective care. We aimed to explore physiotherapy workforce readiness to co-manage consumers with RA by determining the RA-specific professional development (PD) needs in relation to work and educational characteristics of physiotherapists in Western Australia (WA). Methods . An e-survey was sent to physiotherapists regarding their confidence in co-managing people with RA and their PD needs. Data including years of clinical experience, current RA clinical caseload, professional qualifications, and primary clinical area of practice were collected. Results . 273 physiotherapists completed the survey. Overall confidence in managing people with RA was low (22.7–58.2%) and need for PD was high (45.1–95.2%). Physiotherapists with greater years of clinical experience, a caseload of consumers with RA, postgraduate qualifications in musculoskeletal physiotherapy, or who worked in the musculoskeletal area were more confident in managing people with RA and less likely to need PD. Online and face-to-face formats were preferred modes of PD delivery. Discussion . To enable community-based RA service delivery to be effectively established, subgroups within the current physiotherapy workforce require upskilling in the evidence-based management of consumers with RA.